The Effect of Liquidity Ratios and Leverage Ratios on Profitability (Study of PT. Bank Muamalat Indonesia Tbk) - Selvia Depita Sari; Yun Fitriano; Abdul Rahman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study was to determine the extent to which the influence of Liquidity Ratio and Leverage Ratio on Profitability Ratio at PT. Bank Muamalat Indonesia Tbk. The method used in this research is quantitative descriptive, and the variables used are liquidity, leverage and profitability. The data analysis used was multiple linear regression analysis with the help of the SPSS version 23 program. The results show that multiple linear regression Y = -10.501 + 0.084 (X1) + 10.525 (X2) + 8.023, meaning that there is a positive or unidirectional relationship between Liquidity and Leverage on Profitability at PT. Bank Muamalat Indonesia Tbk. Furthermore, partially with the t-test shows that the liquidity variable has a significant effect on profitability because the significance value is 1.413> 0.05 while the leverage variable has a significant effect because the significance value is 1.193> 0.05. While the results of the F test (simultaneous) show that Liquidity and Leverage simultaneously have a significant influence on Profitability of 2.239 because the probability is smaller than the significant value of 0.05.